ANALYSIS OF THE EFFECT OF CASH FLOW COMPONENTS ANACCOUNTING PROFIT ON STOCK PRICES WITH EARNINGS PERSISTENCY AS INTERVENING VARIABLES IN GOODS COMPANIES CONSUMPTION REGISTERED IN INDONESIA STOCK EXCHANGE - karina, dewi (International Journal of Public Budgeting, Accounting and Finance, 2018)
The objective of the research was to examine and to analyze the influence of the components of cash flow (operational cash flow, investment cash flow, and financing cash flow) and accounting profit on stock price with earnings persistence as intervening variable in consumer goods companies listed in the Indonesia Stock Exchange. The research used causal method and secondary data. The population and the samples were 25 consumer goods companies listed in the Indonesia Stock Exchange in the period of 2010-2014. The data were analyzed by using linear regression analysis and path analysis for intervening variable. The result of the research showed that, simultaneously, the components of cash flow (operational cash flow, investment cash flow, and financing cash flow) and accounting profit had significant influence on earnings persistence and stock price. Partially, operational cash flow had positive and significant influence on earnings persistence. Operational cash flow and accounting profit also had positive and significant influence on stock price. It was also found that earnings persistence could only mediate the correlation of the components of cash flow (operational cash flow, investment cash flow, and financing cash flow) with stock price, and it could not mediate the correlation of accounting profit with stock price.